Pelatihan Pembuatan Produk Minuman Kesehatan Berbasis Bahan Alam dan Penyuluhan Regulasi Perijinan SPP IRT - Nafisah Isnawati; Shinta Mayasari; Khrisna Agung; Endang Lifchatullaillah; Helmalia, Helmalia (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The empirical utilization of plants as traditional medicine is still limited to making herbal decoctions which are rather long and on average taste bitter. The development of the utilization from medicinal plants in the form of health drinks that are easy to consume and taste acceptable to the public is still very low. Plant materials that are widely used include kencur in the form of herb beras kencur, temu lawak in the form of herb temu lawak. Therefore, this activity is to improve the health status for the community and increase the economic independence of the community by entrepreneurship with health drinks that are made from natural ingredients with innovative processing. The method that used in is counseling and hands-on practice of making, labeling products. The target audience is people whose daily activities are small entrepreneurs. The results obtained from this activity are increasing knowledge about the utilization of natural ingredients as health drinks, knowledge of SPP-IRT licensing regulations, and processing practices for making, packaging and labeling health drink products in the form of instant beras kencur, instant temu lawak and temu lawak syrup that have worth to sell.